SOLVING DUAL FUZZY NONLINEAR EQUATIONS VIA MODIFIED STIRLING’S METHOD - Umar.A. O; Mamat. M; Waziri. M.Y (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
Stirling’s method is a root finding method designed to approximate a locally unique fixed point and cannot be used to solve fuzzy nonlinear equations. In this paper we present a modified Stirling’s method for solving dual fuzzy nonlinear equations. The fuzzy coefficient is presented in parametric form. Numerical results on some benchmark problems indicate that the proposed method is efficient